Respontivitas Pegawai Negeri Sipil Dalam Pelayanan E-Ktp Di Kantor Dinas Kependudukan Dan Catatan Sipil Kabupaten Enrekang - Apriyadi, Ari; Mahsyar, Abdul; Riskasari, Riskasari (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study was to determine the Respontivity of Civil Servants in E-KTP Services at the Enrekang Regency Population and Civil Registry Office, The number of informants in this study was 6 people. This study used qualitative methods with the type of phemenology research that emphasized the subjectivity of the experience of human life. Data collection techniques used observation, interviews and documentation. Data analysis used interactive analysis models. The results showed that the Civil Service Respontivity in E-KTP Services at the Office of Population and Civil Registration in Enrekang Regency was good but there were still some aspects that were not maximized, this was seen from the aspect of the ability to respond and the accuracy of the waiter was still not optimal because there were still complaints from community related aspects. However, in the aspect of the maximum service timeliness seen from the absence of public complaints about the timeliness of services. Keywords: Responsiveness, e-KTP Services